Preemergence Weed Control with FulTime NXT and Competitive Standards in Grain Sorghum - R. Currie; P. Geier (Kansas Agricultural Experiment Station Research Reports, 2016)
At 71 days after treatment, FulTime NXT (acetochlor + atrazine) at 2.5 or 3.0 qt/a and Lumax EZ (S-metolachlor + atrazine + mesotrione) at 2.0 qt/a were the only treatments to control Palmer amaranth at 90% or more. All treatments provided similar velvetleaf control. Green foxtail control was 75 to 83% with all rates of FulTime NXT or Lumax EZ. Sorghum receiving FulTime NXT at 2.5 or 3.0 qt/a or Lumax EZ yielded significantly more than the control treatments.
Keywords: grain sorghum; preemergence weed control; Palmer amaranth; velvetleaf; puncturevine; green foxtail; FulTime NXT; Acetochlor; Atrazine; Lumax EZ; S-metolachlor; Mesotrione